High-energy particles and radiation in star-forming regions - Bykov, Andrei M.; Kruijssen, Diederik (Space science reviews, 2020)
Non-thermal particles and high-energy radiation can play a role in the dynamical processes in star-forming regions and provide an important piece of the multiwavelength observational picture of their structure and components. Powerful stellar winds and supernovae in compact clusters of massive stars and OB associations are known to be favourable sites of high-energy particle acceleration and sources of non-thermal radiation and neutrinos. Namely, young massive stellar clusters are likely sources of the PeV (petaelectronvolt) regime cosmic rays (CRs). They can also be responsible for the cosmic ray composition, e.g., 22Ne/20Ne anomalous isotopic ratio in CRs. Efficient particle acceleration can be accompanied by super-adiabatic amplification of the fluctuating magnetic fields in the systems converting a part of kinetic power of the winds and supernovae into the magnetic energy through the CR-driven instabilities. The escape and CR propagation in the vicinity of the sources are affected by the non-linear CR feedback. These effects are expected to be important in starburst galaxies, which produce high-energy neutrinos and gamma-rays. We give a brief review of the theoretical models and observational data on high-energy particle acceleration and their radiation in star-forming regions with young stellar population.